Associations between Mental Workload and Sleep Quality in a Sample of Young Adults Recruited from a US College Town. Issue 4 (3rd July 2020) - Jansen, Erica C.; Peterson, Karen E.; O'Brien, Louise; Hershner, Shelley; Boolani, Ali
ABSTRACT: Objective: To evaluate associations between perceived mental workload (number of hours spent studying and perceived mental intensity) and sleep quality among young adults. Participants: 656 participants [62% male, median age (IQR) = 20 (19, 21) years] recruited from a US college town Methods: As part of an online screener, participants answered questions about perceived workload and sleep quality (Pittsburgh Sleep Quality Index (PSQI)). Number of hours/day of mentally engaging work/study, and mental intensity score were the exposures, categorized into quartiles. Linear regression models were used for continuous sleep quality score, and modified Poisson models were used for poor quality sleep (>5 PSQI score) and individual sleep components, adjusting for sex, age, race, physical activity, and caffeine intake. Results: Higher mental work-hours were associated with lower-quality sleep; those in the highest quartile of mental work-hours had a 28% higher likelihood of poor sleep quality (95% CI 2% to 62%). Higher mental intensity scores were also related to lower quality sleep; comparing the highest to the lowest quartiles, there was a 45% higher probability of being a poor sleeper (95% CI 15% to 83%). Associations with PSQI components were partly sex-specific: while both sexes had associations between mental intensity and short sleep, males had positive associations with poor sleep quality and sleep medication use. Conversely, females with higher mental intensity reported higher-quality sleep overall and lower sleep medication use but lower sleep efficiency. Conclusions: Higher mental workload is associated with lower overall sleep quality in young adults. Associations with individual sleep quality components differed by sex.